PERANAN PEJABAT PEMBUAT AKTA IKRAR WAKAF DALAM RANGKA MENERTIBKAN TANAH WAKAF SEBELUM DAN SESUDAH BERLAKUKUNYA PP. 28 TAHUN 1977 - Ria Wulandari (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTLand Replacement before the enactment of PP. 28 Year 1977. Society in Samarinda, especially in sub-district of Samarinda Ulu and North Samarinda Sub-district in repaying their land before the enactment of PP. 28 Year 1977 is done according to customary law which is only based on trust and according to Islamic law hence perwakafan have been considered valid, so that often happened wakaf land in the future due to the status of land that has not get a strong legal certainty (not yet / not yet registered). Soil after the enactment of PP. 28 year 1977. there are still people of Samarinda, especially in Sub Samarinda Ulu and North Samarinda District who do not register their land of wakaf to PPAIW due to economic problems, time and bureaucracy despite the issuance of PP. 28 of 1977 on the representation of land owned and its regulations appointing the Head of Religious Affairs Office (KUA) Kecamatan as Official Wakaf Pledge Officer (PPAIW) who has the main duty and obligation is to make Deed of Wakaf Pledge and apply for registration of wakaf land to Land Office Local district / city.Completion of disputes over the matter of land representation, channeled through the local Religious Courts in accordance with the provisions of applicable laws and regulations. This is in accordance with article 49 paragraph (1) of Law no. 7 of 1989 on Religious Courts which read as follows:The religious courts are on duty and authorized to examine, decide, and resolve cases in the first instance between persons of the faith in their field: Marriage; Inheritance, probate, and grant made under Islamic law; Waqf and shadaah.In the process of certification of wakaf land there are several supporting factors and obstacles in the implementation of such activities. As for the supporting factors are: The existence of good coordination between intalasi / parties concerned so as to create and participate in solving problems related to the implementation of land certification waqf; The existence of funding from the government as a driver to mobilize the active participation of the community towards the financing of registration / certification of wakaf land; The imposition of nadzir and related parties, consultation and counseling meetings.